2016
DOI: 10.1371/journal.pone.0164106
|View full text |Cite
|
Sign up to set email alerts
|

Is the Taklimakan Desert Highway Shelterbelt Sustainable to Long-Term Drip Irrigation with High Saline Groundwater?

Abstract: Freshwater resources are scarce in desert regions. Highly saline groundwater of different salinity is being used to drip irrigate the Taklimakan Desert Highway Shelterbelt with a double-branch-pipe system controlling the irrigation cycles. In this study, to evaluate the dynamics of soil moisture and salinity under the current irrigation system, soil samples were collected to a 2-m depth in the shelterbelt planted for different years and irrigated with different groundwater salinities, and soil moisture and sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…More frequent irrigation schedules (once per 1.5 weeks) have proven better for dealing with drought [12] (Figure 2). Our studies have demonstrated that saline irrigation could significantly influence the dynamics and distribution of soil moisture and salt [13]. Given the buildup of soil salinity through irrigation with saline water, sustainable irrigation strategies are critical to reducing ecological risks [14].…”
Section: Saline Water Irrigation For Shelterbelt Engineering In Desertmentioning
confidence: 82%
See 1 more Smart Citation
“…More frequent irrigation schedules (once per 1.5 weeks) have proven better for dealing with drought [12] (Figure 2). Our studies have demonstrated that saline irrigation could significantly influence the dynamics and distribution of soil moisture and salt [13]. Given the buildup of soil salinity through irrigation with saline water, sustainable irrigation strategies are critical to reducing ecological risks [14].…”
Section: Saline Water Irrigation For Shelterbelt Engineering In Desertmentioning
confidence: 82%
“…This kind of action can ensure the survival of an oasis, and can help jumpstart (i.e., catastrophic shifts) a natural spring that continues to feed an oasis long into the future. Figure 2 is sourced and updated from [13].…”
Section: Saline Water Irrigation For Shelterbelt Engineering In Desertmentioning
confidence: 99%
“…The Taklamakan desert has an average wind speed of 5.6 mph and gale (> 44.7 mph) occurs > 130 days·year −1 ( Lei et al, 2008 ). Soils in the Taklamakan desert are aeolian sandy soils with 87.3% sand, 12.4% silt, and 0.3% clay ( Zhang et al, 2016 ). In 2005, the shrub shelterbelts (72 ~ 78 m in width) were constructed to prevent mobile sand dunes from covering the Tarim desert highway by planting drought and salt tolerant species, such as Haloxylon ammodendron (C. A.…”
Section: Methodsmentioning
confidence: 99%
“…Bunge., Tamarix chinensis Lour., and Calligonum mongolicum Turcz ( Li, 2010 ). Due to the hyper arid environment of the Taklamakan desert, groundwater has been pumped for drip irrigation to water the shelterbelts from March to October regularly ( Zhang et al, 2016 ). The 12-year drip irrigation by using saline groundwater and high evaporation have resulted in soil salinization ( Wang et al, 2012 ), and H. ammodendron becomes the dominant plant species in the shelterbelts ( Li, 2010 ; Zhang et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…The richness and composition of the soil nutrients determine the species, numbers, and activities of the microorganisms [25]. In the Tarim Desert Highway shelterbelt, the irrigation salinity mainly affected the soil salinity in the 0-20 cm range [26]. Therefore, highly saline water used for drip irrigation is not conducive to the survival of microorganisms and adversely affects their functional diversity, genetic diversity, and species diversity in the Tarim Desert Highway shelterbelt.…”
Section: Composition Characters Of Soil Salinitymentioning
confidence: 99%